1995
DOI: 10.1037/0022-0663.87.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Reducing cognitive load by mixing auditory and visual presentation modes.

Abstract: This article reports findings on the use of a partly auditory and partly visual mode of presentation for geometry worked examples. The logic was based on the split-attention effect and the effect of presentation modality on working memory. The split-attention effect occurs when students must split their attention between multiple sources of information, which results in a heavy cognitive load. Presentation-modality effects suggest that working memory has partially independent processors for handling visual and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
420
3
23

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 694 publications
(493 citation statements)
references
References 36 publications
25
420
3
23
Order By: Relevance
“…Experiment 2 extends previous research (Mousavi, Low, & Sweller, 1995) on mixed-modality presentations with diagrams and statements to the context of multimedia learning with animations.…”
Section: Distinguishing Modality and Contiguity Principlesmentioning
confidence: 48%
“…Experiment 2 extends previous research (Mousavi, Low, & Sweller, 1995) on mixed-modality presentations with diagrams and statements to the context of multimedia learning with animations.…”
Section: Distinguishing Modality and Contiguity Principlesmentioning
confidence: 48%
“…These results were at odds with developing literature on animated pedagogical agents (Moreno et al, 2000). Of particular concern, however, was the absence of a general modality effect, inconsistent with dual-mode presentation techniques (e.g., auditory text and visual diagrams) producing typically superior effects compared with conventional, single-modality formats (e.g., visual test and visual diagrams) or visual-only formats (Moreno et al, 2000;Mousavi et al, 1995;Tindall-Ford, Chandler, & Sweller, 1997). At least two factors could potentially have contributed to the lack of significance in this experiment: low power due to small sample size or a problem with the design of the instructional material.…”
Section: Pilot Studymentioning
confidence: 99%
“…Specifically, does an agent's image foster or hinder learning when it is programmed to explain additional visual information aurally-for instance, a set of problem states contained in an example-that appears on the screen simultaneously with the agent itself? Despite the empirical evidence that there is an increased cognitive capacity because the information is distributed across two working memories-verbal and visual working memories-as opposed to one, by using a dual-mode format in examples (Mousavi et al, 1995), the visual presence of the agent might be detrimental to learning by competing with the other visual information for the learner's limited cognitive resources (Sweller, 1999). Indeed, Jeung and his colleagues (Jeung, Chandler, & Sweller, 1997) found that when the learning task involved visually complex, unfamiliar material, the superiority of dual-mode examples disappeared and only reappeared if the examples were restructured to include visual indicators-such as electronic flashing or animation-designed to draw attention to the visual segment of the example being alluded to by synchronized, aurally presented statements.…”
Section: Overview Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that modalities help to increase memory. When activating both auditory and visual resources for presentations, modalities help to increase long-term memory [20].…”
Section: Modality Principlementioning
confidence: 99%